2016
DOI: 10.1038/cdd.2015.167
|View full text |Cite
|
Sign up to set email alerts
|

Aiolos collaborates with Blimp-1 to regulate the survival of multiple myeloma cells

Abstract: The transcriptional repressor B lymphocyte-induced maturation protein-1 (Blimp-1) has crucial roles in the control of plasma cell differentiation and in maintaining survival of plasma cells. However, how Blimp-1 ensures the survival of plasma cell malignancy, multiple myeloma (MM), has remained elusive. Here we identified Aiolos, an anti-apoptotic transcription factor of MM cells, as a Blimp-1-interacting protein by mass spectrometry. ChIP coupled with DNA microarray was used to profile the global binding of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…in particular, PRDI-BF1 is required for XBP-1 induction, a transcriptional activator necessary for plasma cell survival because reduction levels of activated XBP1 determined by proteasome inhibitors causes rapidly cell apoptosis. 7 PRDI-BF1 and the PRDI-BF1β can be considered a crucial point for understanding efficacy and limits of many new drugs used in MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in particular, PRDI-BF1 is required for XBP-1 induction, a transcriptional activator necessary for plasma cell survival because reduction levels of activated XBP1 determined by proteasome inhibitors causes rapidly cell apoptosis. 7 PRDI-BF1 and the PRDI-BF1β can be considered a crucial point for understanding efficacy and limits of many new drugs used in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, lenalidomide-induced cell death was partially rescued by reintroduction of PRDI-BF1. 5 , 7 Anyway, no data are still available about the different expressions of PRDI-BF1 and its isoform beta during the clinical evolution and the management of Myeloma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Conery et al The MM specific IRF4 aberrant downstream transcriptional network could also represent a valid target for inhibition. Previous studies reported that knockdown of Blimp1 by short hairpin RNA causes apoptosis in MM cells [68] and that the interaction between Ailos and Blimp1 plays an important role in MM cells survival, probably through the collaborative down-regulation of proapoptotic genes [69]. Moreover, treatment with IMiD lenalidomide caused proteasomal degradation of Blimp1 and reduced Aiolos levels leading to apoptosis of MM cells [69].…”
Section: Targeting the Irf4 Transcriptional Network In Multiple Myelomamentioning
confidence: 96%
“…The regulatory motif of IRF4 overlaps with that of Blimp-1, and Aiolos contributes to Blimp-1 function. 39 Thus, each Ikaros family member likely involves nonoverlapping roles in IRF4 and Blimp-1-dependent PC differentiation.…”
Section: Discussionmentioning
confidence: 99%